Case report: Advanced age at transplantation and pre-emptive treatment with dupilumab in DOCK8 deficiency - Trombello, Sophia; Jarisch, Andrea; Willasch, Andre; Rettinger, Eva; Fekadu-Siebald, Julia; Holzinger, Dirk; Adelmann, Roland; Bader, Peter; Bakhtiar, Shahrzad (Frontiers in Immunology, 2025)
Dedicator of cytokinesis 8 (DOCK8) deficiency is a combined immunodeficiency (CID) due to biallelic mutations in the gene encoding DOCK8. Major clinical phenomena are recurrent severe infections of the lungs and skin, atopic eczema, and predisposition to malignancy leading to a poor prognosis. Typical findings include highly elevated IgE and eosinophilia. Allogeneic hematopoietic stem cell transplantation (alloHSCT) is indicated as the only curative treatment option. We present a patient with advanced disease undergoing alloHSCT at the age of 11 years after individualized pre-treatment using dupilumab and rituximab resulting in a decrease in IgE levels and clinical improvement of the skin condition. Additionally, in a review of the literature, we summarize morbidity and outcome in DOCK8-deficient patients older than 8 years of age receiving alloHSCT. Life-threatening infections, malignancy, and disease-related complications with organ damage pre-transplant are challenging in older DOCK8-deficient patients. The therapeutic role of dupilumab in DOCK8 deficiency should be evaluated in larger studies.